Pioneers of modern typography Spencer Herbert. - Spencer, Herbert 1924-2002 (Lund Humphries, 2004)
Modern typography does not have its origins in the conventional printing industry, instead, its roots are entwined with those of 20th-century painting, poetry and architecture. This text examines what led up to the new concepts in graphic design and carefully disentangles the various influences.